The Effect of Supervisors Feedback in Extended Teaching on Pre-Service Mathematics Teachers Practice - , Augustine Boadi; , Esther Amoah; , Evelyn Serwaa Ameyaw; , Evans Atteh (Archives of Current Research International, 2024)
This study examined the influence of supervisor feedback on the teaching practices of pre-service mathematics teachers during Extended Teaching (off-campus teaching practice). The research design adopted for the study was action research. The target population was level 400 students of a College of Education and the population size was three hundred and ninety-two (392) whilst the sample size was sixty-three (63), comprising of pre-service mathematics teachers, which was selected based on purposive sampling. The instruments used for the study were Intern Teaching Assessment Form (ITAF) and Teaching Evaluation Comment Form (TECF). In the pre-intervention stage, a first supervision was conducted to identify the strength and weaknesses of the students before the feedback from the observation was discussed and reflections were held with the pre-service teachers to serve as the intervention. A second supervision was conducted to evaluate the intervention strategies. The results of the study showed a significant improvement in students’ second supervision scores (M=71.0000) compared to the first supervision scores (M=64.8033). A third supervision was conducted 7 weeks after the second supervision using ITAF and TECF to check students’ retention of teaching skills and knowledge, which the result showed no significant improvement in pre-service mathematics teachers’ second supervision scores (M=71.0000) compared to the third supervision scores (M=71.1475), indicating pre-service mathematics teachers’ retention of the teaching skills and knowledge had been exceptionally good. Supervisors' post-observation feedback enhances pre-service mathematics teachers' interpersonal communication, classroom management, student support strategies, leadership, and practical knowledge of standard-based curriculum implementation, thereby improving their instructional style. The study recommends the extension of the Extended Teaching duration to encompass an entire academic year in order to enhance the practical component of the preservice teacher training program and potentially impact the quality teaching and learning policy agenda.